Intrinsic Enhancement of Dielectric Permittivity in (Nb + In) co-doped TiO2 single crystals - Masaru Kawarasaki; Kenji Tanabe; Ichiro Terasaki; Yasuhiro Fujii; Hiroki Taniguchi (Scientific Reports, 2017)
Abstract The development of dielectric materials with colossal permittivity is important for the miniaturization of electronic devices and fabrication of high-density energy-storage devices. The electron-pinned defect-dipoles has been recently proposed to boost the permittivity of (Nb + In) co-doped TiO2 to 105. However, the follow-up studies suggest an extrinsic contribution to the colossal permittivity from thermally excited carriers. Herein, we demonstrate a marked enhancement in the permittivity of (Nb + In) co-doped TiO2 single crystals at sufficiently low temperatures such that the thermally excited carriers are frozen out and exert no influence on the dielectric response. The results indicate that the permittivity attains quadruple of that for pure TiO2. This finding suggests that the electron-pinned defect-dipoles add an extra dielectric response to that of the TiO2 host matrix. The results offer a novel approach for the development of functional dielectric materials with large permittivity by engineering complex defects into bulk materials.